Why do tenants leave social housing? Exploring residential and social mobility at the lowest rungs of Australia's socioeconomic ladder. Issue 4 (December 2015) - Wiesel, Ilan; Pawson, Hal
Abstract : Historically, social housing in Australia operated as a springboard for social mobility. For many working families, public housing tenancy was an opportunity to save for a house purchase deposit. Latterly, tenant exits from public to private housing have declined to very low levels. This has raised concerns about systemic barriers to residential and social mobility for social renters, and about the consequent longer waiting times for applicants in need of social housing. Drawing on administrative data collected by social housing providers in NSW and Victoria, and in‐depth interviews with 95 former and current social housing tenants in both states, this paper examines tenant attitudes, intentions and motivations as regards future house‐moves. We argue that the primary disincentives to exit relate to affordability and security of tenure in private rental, rather than factors related to the social housing system itself.